Complexity and Entropy in Legal Language - Friedrich, Roland (Frontiers in Physics, 2021)
We study the language of legal codes from different countries and legal traditions, using concepts from physics, algorithmic complexity theory and information theory. We demonstrate that the vocabulary entropy, which measures the author’s diversity in word choice, combined with the compression factor, which is derived from a lossless compression algorithm and which measures the redundancy present in a text, are well suited to separate different writing styles in different languages, in particular also legal language. We show that different types of (legal) text, e.g. acts, regulations or literature, are located in distinct regions of the complexity-entropy plane, spanned by the information and complexity measure. Therefore, this two-dimensional approach already gives novel insights into the drafting style and structure of statutory texts, complementing other methods.